Pulpochoque: un caso de responsabilidad empresarial - Solano, David (2006)
As in many other localities within Peru, Pulpochoque received investments that did not generate population development, as said investment were economic-oriented and did not take into account the needs of people. The gap between the interests of both actors (the company vs. the people), deepened by personal feelings, created an attitude of rejection towards Chochomin mining company (Chinese capitals) and its staff. Julio Concha, the company’s new head of community relations, has to face this hard situation and restart activities that were paralyzed by the population. This case is based on real facts and shows that personal attitudes and approach can often be keys to open or chains to close the doors of social consensus activities.